2021
DOI: 10.1075/task.00005.duo
|View full text |Cite
|
Sign up to set email alerts
|

Learning vocabulary in spoken input- and output-based tasks

Abstract: This experimental study explores the differential effects of spoken input-based and output-based tasks on vocabulary knowledge. The study also investigates whether such tasks result in more learning gains than exposure to input-only (no subsequent task). The study employed a pretest-posttest design with two groups: an experimental group (n = 32) who completed both input- and output-based tasks in a counterbalanced way and a comparison group (n = 12) who were only exposed to L2 input. Vocabulary gains were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The findings showed that both task types resulted in vocabulary uptake, but input-based tasks resulted in higher gains for learning the meaning of English vocabulary, and output-based tasks led to more gains for learning the form of English vocabulary. The positive effects of both task types on vocabulary learning were also reported in Duong et al [17], which focused on spoken tasks and spoken vocabulary knowledge.…”
Section: Research Into Vietnamese Efl Learners' Vocabulary Acquisitionsupporting
confidence: 73%
See 4 more Smart Citations
“…The findings showed that both task types resulted in vocabulary uptake, but input-based tasks resulted in higher gains for learning the meaning of English vocabulary, and output-based tasks led to more gains for learning the form of English vocabulary. The positive effects of both task types on vocabulary learning were also reported in Duong et al [17], which focused on spoken tasks and spoken vocabulary knowledge.…”
Section: Research Into Vietnamese Efl Learners' Vocabulary Acquisitionsupporting
confidence: 73%
“…While research on L2 vocabulary learning in other contexts might be useful and applicable, studies that have a specific focus on Vietnamese EFL learners have their own values, because language learning might vary among learners of different contexts. To date, such studies have focused on the effects of different types of input [12][13][14][15], focused tasks [16,17], computerassisted language learning [18], and explicit instruction [19] on Vietnamese EFL learners' vocabulary acquisition.…”
Section: Research Into Vietnamese Efl Learners' Vocabulary Acquisitionmentioning
confidence: 99%
See 3 more Smart Citations